Beastly - Flinn, Alex (New York Harper Teen, 2007)
New York City. A humiliated witch casts a spell on popular Kyle Kingsbury and transforms him into a beast. Banished from his home, Kyle prowls at night, waiting for true love's kiss to break his curse. Some strong language.
Keywords: Beauty, Personal -- Young adult fiction -- New York